Porous Fibers Composed of Polymer Nanoball Decorated Graphene for Wearable and Highly Sensitive Strain Sensors. (5th August 2019) - Huang, Tao; He, Peng; Wang, Ranran; Yang, Siwei; Sun, Jing; Xie, Xiaoming; Ding, Guqiao
Abstract: Wearable textile strain sensors that can perceive and respond to human stimuli are an essential part of wearable electronics. Yet, the detection of subtle strains on the human body suffers from the low sensitivity of many existing sensors. Generally, the inadequate sensitivity originates from the strong structural integrity of the sensors because tiny external strains cannot trigger enough variation in the conducting network. Inspired by the rolling friction where the interaction is weakened by decreasing interface area, porous fibers made of graphene decorated with nanoballs are prepared via a prolonged phase‐separation process. This novel structure confers the graphene fibers with high gauge factors (51 in 0–5% and 87 in 5–8%), which is almost 10 times larger than the same structures without nanoballs. A low detection limit (0.01% strain) and good durability (over 6000 circles) are obtained. By the virtue of these qualities, these fiber‐based textile sensors can recognize a pulse wave and eyeball movement in real‐time while keeping comfortable wearing sense. Moreover, by weaving such fibers, the electronic fabrics with a specially designed structure can distinguish the multilocation in real time, which shows great potential as wearable electronics. Abstract : The proposed interconnection weakening strategy can effectively increase the sensitivity of graphene‐polymer composite fiber‐based strain sensors by replacing the panel‐inserting structure with a nanoball‐decorating frame. The obtained fibers show a high gauge factor of 87 and low detection limit of 0.01%, which also allows for the fabrication of wearable electronic fabrics with excellent performance.